Penanaman Karakter dalam Pendidikan Kewarganegaraan - Amelia Putri Wulandari; Dinie Anggraeni Dewi (Civiliza Publishing, 2021)
Citizenship education is an educational process to build exemplary, willingness, and the ability of individuals or students to develop creativity that reflects the national identity which requires socio-cultural values. In the context of national and character development, civic education has a very important position, function and role in the life of the nation and state. The method used is a literature review of various writings, both books and journals related to the implementation of character in Citizenship Education based on strengthening character education. There are three main approaches to character education, namely the first one is the cognitive development, approach the caring approach, and the traditional character education. Citizenship education provides provisions for citizens in terms of intellectual intelligence, emotional intelligence, social intelligence, and spiritual intelligence.